Effects of resveratrol on macrophages after phagocytosis of Candida glabrata - Zong-Han Chen; Meng Guan; Wei-Jia Zhao (Elsevier, 2023)
Candida glabrata is believed to be the underlying cause of many human ailments, including oral, gastrointestinal, and vaginal disorders. C. glabrata-caused deep-seated infections, coupled with its resistance to antifungal drugs, may contribute to a high mortality rate. Resveratrol is a polyphenol and can achieve better therapeutic effects when administered in combination with micafungin, but the underlying molecular mechanisms remain unknown. Here, we investigate the effects of varying doses of resveratrol on the proliferation, apoptosis, and activity of macrophages, which were co-cultured with micafungin-pretreated C. glabrata. Resveratrol can restore the decreased proliferative activity of macrophages caused by the phagocytosis of C. glabrata. Further investigations demonstrated that this restoration ability exhibited a dose-dependent manner, reaching the highest level at 200 µM of resveratrol. Resveratrol tended to be more effective in inhibiting macrophage apoptosis and reducing reactive oxygen species (ROS) levels with concentration increases. In addition, at medium concentrations, resveratrol may down-regulate the expression of most inflammatory cytokines, whereas at high concentrations, it started to exert pro-inflammatory functions by up-regulating their expressions. Macrophages may shift from an anti-inflammatory (M2) phenotype to an inflammatory (M1) phenotype by resveratrol at 200 µM, and from M1 to M2 at 400 µM. Our research shows that resveratrol with micafungin are effective in treating C. glabrata infections. The resveratrol-micafungin combination can reduce the production of ROS, and promote the proliferation, inhibit the apoptosis, and activate the polarization of macrophages in a dose-dependent manner. This study offers insights into how this combination works and may provide possible direction for further clinical application of the combination.